Interference caused by first language on the pronunciation of english voiced / voiceless fricative and affricate consonant sounds /d/, /θ/, /tʃ/, and / ʃ /: a literature review work supported with some field data collected among students of the b.a. in english emphasis on teaching of the Foreign Languages Department of the University of El Salvador, Semester II – 2011 - López Rivas, María Roxana
The purpose of this study is to describe how mother tongue can interfere in second language pronunciation. Even though the mother tongue can interfere in different ways when learning a foreign or second language, this work concentrates on how first language interferes in the pronunciation of the target language especially in the pronunciation of fricative and affricate sounds /d/, /θ/, /tʃ/, and / ʃ /. Therefore, a research in which these sounds are transferred from L1 when learning English as a foreign language was carried out based on the importance that reaching a high level of performance in a second or foreign language implies.